(untitled) (Minerva, 2019)
The author of this of this paper provides a new hypothesis about the plot of Epicharmus’ drama Τριακάδες:. Taking into account the play’s title, some internal evidence, and certain parallels from other Greek comic works, the author suggests that the drama could have dealt with the troubles of some character obliged to pay his debts at the end of the month. The topic of debts and debtors has also parallels in other plays by Epicharmus himself.